Translating Tourism Brochures by the 4th-Year English Education Students: Quality and Problems - Febrina, Vivi; Oktavia, Witri (Journal of English Language Teaching, 2025)
Translation is a crucial skill for English Education students, specifically when it comes to practical texts like tourism brochures. This study investigated the quality and problems in students’ translation results of tourism brochures from Indonesian to English. Conducting a descriptive approach, the assessment was based on Nababan et al. (2012) for analyzing translation quality and Mathieu (2003) for identifying translation problems. 22 fourth-year English Education students of Universitas Negeri Padang were instructed to translate seven tourism brochure passages. The analysis revealed that the overall students’ translation was fair, with an average score of 2.27, consisting of noticeable problems in accuracy, acceptability, and readability. Moreover, 456 data of identified problems were found, with 175 data (38.37%) of word-choice problems and 131 data of grammatical problems being the most prevalent. There are also problems in cultural with 77 data (16.88%), rhetorical with 53 data (11.62%), and pragmatic with 20 data (4.38%). These findings suggest that students struggled in producing a natural translation of tourism brochures, especially in choosing appropriate equivalents and grammatical construction.